Wnioski i refleksje wynikające z ewaluacji II Łódzkiego Panelu Obywatelskiego - Brzeziński, Kamil; Jurczak, Tomasz; Rzeńca, Agnieszka; Agnieszka Gralak (Public participation in urban climate policy making: The example of Lodz, 2024)
In recent years, two thematically related citizens’ assemblies have been implemented in Lodz, focusing on the mitigation and adaptation of the city to climate change, and consequently, improving the quality of life for its residents. The first panel addressed greenery in the city, while the second focused on finding answers can the question: “How to reduce harmful greenhouse gas emissions in Lodz by 55% by 2030?”. This chapter presents and discusses the key results of the evaluation survey conducted with the participants of II ŁPO. The objective of this chapter is to provide practical knowledge and enrich the experiences of cities authorities in conducting social participation processes, utilizing the citizens’ assembly as an instrument of urban policy.